2020
DOI: 10.14309/ctg.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Serum Autoantibodies Against Tumor-Associated Antigens as Biomarkers in Gastric Adenocarcinoma Based on the Focused Protein Arrays

Abstract: INTRODUCTION: Previous studies have demonstrated that autoantibodies against tumor-associated antigens (TAAs) in patients with cancer can be used as sensitive immunodiagnostic biomarkers for the detection of cancer. Most of these TAAs are involved in the tumorigenesis pathway. Cancer driver genes with intragenic mutations can promote tumorigenesis. This study aims to identify autoantibodies against TAAs encoded by cancer driver genes in sera as potential immunodiagnostic biomarkers for gastric ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Early detection is one of the most promising approaches to improve clinical outcomes for patients with cancer. Considerable efforts have been made to develop more sensitive and specific tests to detect cancer with different combinations of autoantibodies (6,(26)(27)(28). Because of its high sensitivity to early gastric cancers, serum WT1-271 IgM antibody may be used as a detection marker in the screening of gastric cancer in combination with autoantibodies, especially in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection is one of the most promising approaches to improve clinical outcomes for patients with cancer. Considerable efforts have been made to develop more sensitive and specific tests to detect cancer with different combinations of autoantibodies (6,(26)(27)(28). Because of its high sensitivity to early gastric cancers, serum WT1-271 IgM antibody may be used as a detection marker in the screening of gastric cancer in combination with autoantibodies, especially in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies showed that combining multiple biomarkers can remarkably improve the diagnostic accuracy and speci city in different cancerous diseases, such as OC, BC, ESCC, gastric cancer (GC) and LC [17,[21][22][23][24][25]. Jiang et al utilized decision tree method to construct a diagnostic panel consist of seven TAAbs (TP53, NPM1, FGFR2, PIK3CA, GNA11, HIST1H3B, and TSC1) with the AUC of 0.897 and sensitivity and speci city of 94.4% and 84.9% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, WGCNA is an excellent algorithm in screening the biological markers, and it has been used in many studies 26 . The human proteomics chip contains 21 000 human recombinant proteins in this study, which can comprehensively screen TAAs 53‐56 . In summary, bioinformatics can screen for genes that play important roles in the occurrence and development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 26 The human proteomics chip contains 21 000 human recombinant proteins in this study, which can comprehensively screen TAAs. 53 , 54 , 55 , 56 In summary, bioinformatics can screen for genes that play important roles in the occurrence and development of HCC. Hence, those two methods were used together to screen valuable TAAs as much as possible.…”
Section: Discussionmentioning
confidence: 99%